2011
DOI: 10.1111/j.1398-9995.2010.02527.x
|View full text |Cite
|
Sign up to set email alerts
|

NOD-like receptors in the human upper airways: a potential role in nasal polyposis

Abstract: The present study demonstrates the presence of NLRs in several upper airway tissues and highlights a potential role of NLRs in chronic rhinosinusitis with polyps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 35 publications
2
41
0
Order By: Relevance
“…Relevant to our finding of NRLP3 in the normal mouse bronchiolar epithelium is the recent observation reporting NRLP3 and two other NLRs (NOD1 and NOD2) in upper airway human tissues including normal nasal mucosa, nasal polyps, tonsils, and adenoids [29]. It is likely therefore that inflammasome components are present along the entire length of the airways and constitute a front-line defence.…”
Section: Discussionsupporting
confidence: 66%
“…Relevant to our finding of NRLP3 in the normal mouse bronchiolar epithelium is the recent observation reporting NRLP3 and two other NLRs (NOD1 and NOD2) in upper airway human tissues including normal nasal mucosa, nasal polyps, tonsils, and adenoids [29]. It is likely therefore that inflammasome components are present along the entire length of the airways and constitute a front-line defence.…”
Section: Discussionsupporting
confidence: 66%
“…It has previously been reported that high NLRP3 mRNA levels were detected in neutrophils, macrophages [2], and primary immune cells [14], while NLRP3 protein was only detected in lymphoid tissues by western blot, and not by IHC, using an in-house generated monoclonal antibody. In 2011, Månsson et al [16] reported that NALP3 mRNA and protein were present in nasal polyps and normal nasal mucosa in upper airways. Currently, there are no detailed tissue distribution data pertaining to NLPR3 in BALB/c mice.…”
Section: Discussionmentioning
confidence: 99%
“…These NLR receptors (NOD-like receptors) are found within the cytoplasm of cells and can also be triggered by microbial-derived factors [1]. Three of these receptors (NOD-1, NOD-2, and NALP-3) were investigated in NP and were shown to be highly enriched in the epithelia of patients relative to healthy controls and shown to be downregulated by steroid treatment [27]. In addition to the NLR class of receptors, an as-yet-unknown receptor is held responsible for the detection and responsiveness of airway epithelia to chitin [28].…”
Section: Chronic Rhinosinusitis and The Outside Microbial Worldmentioning
confidence: 99%
“…This would tie in with the observation that epithelial cells isolated from nonresponsive polyps (return of visible polyps within 6 months after surgery despite postoperative use of local and oral steroids) showed higher basal mRNA levels of IL-33 than epithelial cells isolated from responsive polyps [25, 62]. Moreover, reports show that downstream of ILC2s, CRS with NP is associated with lower levels of expression of the epithelial IL-22 receptor compared with healthy individuals or CRS patients without NP [63], and that polymorphisms in the gene are correlated with disease severity [27]. Given the ability of nasal epithelial cells to respond to IL-13 and IL-22, such a potential should consider that IL-33 can also be produced by fibroblasts and that IL-33 receptors can also be found on mast cells, eosinophils, and Th2 lymphocytes [12].…”
Section: A New View On Innate Immunity and Chronic Rhinosinusitismentioning
confidence: 99%